Research on the spatial characteristics of urban integration from multi-dimensions: A case study in the Guangzhou-Qingyuan metropolitan area - Tang, Bo; Huang, Zhangdi (Frontiers in Earth Science, 2023)
The urban integration of metropolitan areas is an essential embodiment of the high-quality development of urban agglomerations. Using 2012-2020 NPP-VIIRS night light, social economy, OpenStreetMap (OSM), Baidu migration, and other data, using geographic information methods, commodity urban integration index, industrial structure similarity index, and other methods, to explore the characteristics of Guangzhou-Qingyuan's urban integration from four dimensions, such as economic development, industrial structure, transportation facilities, and public services, and the results show that: (1) Economic dimension: The southeast is high light value, and the northwest is low light value. The commodity urban integration index is increasing, the market segmentation degree is gradually shrinking, and the commodity market urban integration level continues to improve. (2) Industrial dimension: The similarity coefficient of the industrial structure is between 0.94 and 0.96, and the industrial structure develops from convergence to divergence. However, the leading industries are not the same, and the industrial demands are misplaced to realize the industry's coordinated development. (3) Transportation dimension: The number of roads in Guangzhou-Qingyuan increases, and the road density increases, but the road density level does not change significantly. Transportation accessibility presents a circle-layer structure as a whole, and the transportation accessibility at the boundary area between the two places has been dramatically improved. (4) Dimension of public service facilities: There is a noticeable trend of urban integration. Due to the close links between the historical foundation and social culture, inter-city people flow frequently, but the relevant infrastructure needs to be improved urgently.